2021
DOI: 10.2337/dc21-1023
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Insulin Clearance as the Initial Regulator of Obesity-Associated Hyperinsulinemia: Novel Insight Into the Underlying Mechanism Based on Serum Bile Acid Profiles

Abstract: To investigate the roles of insulin clearance and insulin secretion in the development of hyperinsulinemia in obese subjects and to reveal the association between insulin clearance and bile acids (BAs). RESEARCH DESIGN AND METHODSIn cohort 1, insulin secretion, sensitivity, and endogenous insulin clearance were evaluated with an oral glucose tolerance test in 460 recruited participants. In cohort 2, 81 participants underwent an intravenous glucose tolerance test and a hyperinsulinemic-euglycemic clamp to asses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“… 17–19 In addition, if excessive accumulation of visceral fat leads to the impairment of insulin clearance and transmission of signaling pathways in pancreatic islets, it affects the energy supply of the kidneys which, eventually, leads to kidney damage. 20–22 In our study, levels of TG, FPG, and HOMA-IR were increased in the CKD group, and the differences were significant. In the HOMA-IR subgroup, the CKD risk increased by 2.43-times for each SD increase in METS-VF.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“… 17–19 In addition, if excessive accumulation of visceral fat leads to the impairment of insulin clearance and transmission of signaling pathways in pancreatic islets, it affects the energy supply of the kidneys which, eventually, leads to kidney damage. 20–22 In our study, levels of TG, FPG, and HOMA-IR were increased in the CKD group, and the differences were significant. In the HOMA-IR subgroup, the CKD risk increased by 2.43-times for each SD increase in METS-VF.…”
Section: Discussionsupporting
confidence: 49%
“…Impairment of insulin clearance in obese individuals, and the accompanying insulin resistance and disorders of glucose metabolism in tissues and organs, promote morbidly obesity. 20 , 27 Increased circulating levels of TGs, decreased clearance of LDL-C, and long-term maintenance of lower levels of HDL-C are involved in obesity development. 28 , 29 METS-VF integrates the above parameters stated above to assess the metabolic status of visceral fat, which can reflect the risk of human disease to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired insulin clearance is an important factor causing increased serum insulin levels, which can be a cause of insulin resistance. [14,30,31] Therefore, we investigated the insulin clearance in HFD-induced obese and control mice. After an insulin challenge for the indicated times (15, 30, and 60 min), insulin levels were significantly greater in HFD-fed obese than chow diet-fed mice (Figure 1G).…”
Section: Impaired Insulin Clearance In Hfd-fed Obese Micementioning
confidence: 99%
“…[ 13 ] A recent study found that hyperinsulinemia in obese subjects may be caused primarily by impaired insulin clearance rather than by increased insulin secretion. [ 14 ] Thus, the current evidence suggests that impaired insulin clearance is not only a consequence but also a major and independent cause of insulin resistance. [ 15 ] Moreover, previous studies have also shown that HFD and cafeteria diet, which more closely resemble Western diet, lead to impaired insulin clearance in mice.…”
Section: Introductionmentioning
confidence: 99%